Hybrid M13 bacteriophage-based vaccine platform for personalized cancer immunotherapy. (October 2022) - Dong, Xue; Pan, Pei; Ye, Jing-Jie; Zhang, Qiu-Ling; Zhang, Xian-Zheng
Abstract: Although cancer vaccines exhibit great advances in the field of immunotherapy, developing an efficient vaccine platform for personalized tumor immunotherapy is still a major challenge. Here we demonstrate that a bioactive vaccine platform (HMP@Ag) fabricated with hybrid M13 phage and personal tumor antigens can facilitate delivery of antigens into lymph nodes and activate antigen-presenting cells (APCs) through the Toll-like receptor 9 (TLR9) signaling pathway, which boosts both innate and adaptive immune response. As an adjuvant platform, hybrid M13 phages can deliver various tumor-specific antigens through simple adsorption to support the current development of personalized vaccines for cancers. Notably, the HMP@Ag vaccine not only prevented the tumors, but also delayed the tumor growth in established (subcutaneous and orthotopic) and metastatic tumor-bearing models while synergy with immune checkpoint blockade (ICB) therapy. Moreover, HMP@Ag triggered a robust neoantigen-based specific immune response in tumor-specific mutation models. In a clinically relevant surgery model, using autologous cell membrane from primary tumors-based HMP@Ag cooperation with ICB dramatically inhibited the post-operation recurrence, and elicited a long-term immune memory effect simultaneously. These findings imply that the M13 phage represents a powerful tool to develop a bio-activated hybrid platform for personalized therapy.